Bioactivity Fraction of Methanolic Seed Extract of Barringtonia asiatica L. (Kurz.) (Lecythidaceae) Against Spodoptera litura F. (Lepidoptera: Noctuidae) - Teddy Budiyansyah; Danar Dono; Rika Meliansyah; Unang Supratman (CROPSAVER, 2018)
Water seed extract of Barringtonia asiatica was used as fish poison by traditional community. This study aims to determine the bioactivity of methanolic seed extract fraction of B. asiatica against S. litura. The extract tested was spread evenly on the leaf surface by using microsyringe. The experiment consisted of 12 treatments and 3 replications. Treatments were concentration of 0.3% and 0.1% of fraction 16, 17, 18, 19, 20 of methanolic seed extract of B. asiatica, and concentration of 0.264% methanolic seed extract of B. asiatica; and control. The results showed that the fraction 19 (20% EtOAc and 80% MeOH eluent) of methanol extract of B. asiatica seed has the highest bioactivity against the larvae of S. litura. The fraction 19 of methanolic seed extract of B. asiatica had LC50 value of 0.182% at 12 days after treatment. In addition, the 19 fraction of methanolic seed extract of B. asiatica decreased food intake, weight and lengthened development time of larvae.Keywords : Barringtonia asiatica, bioactivity, fraction, Spodoptera litura.